2017
DOI: 10.1093/heapol/czw170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of integrated microfinance and health interventions: an updated review of the evidence

Abstract: Integrated microfinance and health education programs were effective, though longer intervention periods are necessary to measure more complex pathways to health status. The effect of microfinance combined with other health components was less clear. Stronger randomized research designs with multiple study arms are required to improve evidence and disentangle the effects of multiple component microfinance and health interventions. Few studies attempted to understand changes in economic outcomes, limiting our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 52 publications
2
50
1
1
Order By: Relevance
“…One explanation could be the focus onSouth Asia, because Duvendack et al (2011) pool of included primary studies was dominated by evidence from South Asia while Gopalaswamy et al (2016) had a sole focus on South Asia.However, none of the correlations in the pool of medium-and high-confidence studies exceeded 50%, which is different for the 21 low confidence studies (see Appendix 6 for details), where we found correlations of up to 83% (betweenAwaworyi et al 2014Awaworyi et al , 2016 and 71% (betweenAwaworyi et al 2014;Awaworyi Churchill et al, 2015). The correlation betweenAwaworyi et al (2016) andMaitrot andNiño-Zarazúa (2017) is 67% and correlations between Maitrot and Niño-Zarazúa (2017),Awaworyi et al (2014) andYang and Stanley (2013) are 83% Lorenzetti et al (2017). andArrivillaga and Salcedo (2014) are correlated by 43%.…”
mentioning
confidence: 57%
“…One explanation could be the focus onSouth Asia, because Duvendack et al (2011) pool of included primary studies was dominated by evidence from South Asia while Gopalaswamy et al (2016) had a sole focus on South Asia.However, none of the correlations in the pool of medium-and high-confidence studies exceeded 50%, which is different for the 21 low confidence studies (see Appendix 6 for details), where we found correlations of up to 83% (betweenAwaworyi et al 2014Awaworyi et al , 2016 and 71% (betweenAwaworyi et al 2014;Awaworyi Churchill et al, 2015). The correlation betweenAwaworyi et al (2016) andMaitrot andNiño-Zarazúa (2017) is 67% and correlations between Maitrot and Niño-Zarazúa (2017),Awaworyi et al (2014) andYang and Stanley (2013) are 83% Lorenzetti et al (2017). andArrivillaga and Salcedo (2014) are correlated by 43%.…”
mentioning
confidence: 57%
“…Several reviews on microfinance indicate its important effects on health awareness and care seeking. While some reviews affirm impacts on health outcomes, others are more cautious, suggesting the need for further longitudinal research to evaluate impact pathways and effects [37][38][39].…”
Section: Enabling Community Savings and Transport Groupsmentioning
confidence: 99%
“…The correlation between Awaworyi et al (2016) and Maîtrot & Niño-Zarazúa (2017) is 67 percent and correlations between Maîtrot & Niño-Zarazúa (2017), Awaworyi et al (2014) and Yang et al (2013) are 83 percent. Lorenzetti et al (2017) and are correlated by 43 percent. We would have certainly excluded at least one of the Awaworyi studies on the basis of these findings, but given they are both low-confidence, this was not necessary.…”
Section: Independence Of Reviews -Overlapmentioning
confidence: 99%
“…Year Main research question What is the extent to which MHI has contributed to providing financial risk protection to low-income households in developing countries? Lorenzetti et al 2017 What is the effect of integrated microfinance and health programs? Cole et al 2012 What is the effectiveness of index-based insurance in helping the developing country poor manage weather-related risk?…”
Section: Appendix B: Mecir Checklistmentioning
confidence: 99%